Melampaui Amal Tradisional: Pengembangan Model Implementasi Konservasi Ekologis Berbasis Infak dalam Filantropi Islam di Indonesia - Annisa Sayyid; Slamet Haryono; Sunaryati Sunaryati; Misnen Ardiansyah (Syariah: Jurnal Hukum dan Pemikiran, 2026)
The global ecological crisis demands the mobilization of alternative resources for environmental conservation, yet the potential of Islamic philanthropy, such as infaq in Indonesia, remains underoptimized. Infaq funds reach Rp 20 trillion annually, but only 5% is allocated to the environment, despite 78% of Muslims acknowledging conservation as part of their religious responsibility. This gap is exacerbated by the absence of an operational framework: only 12% of 847 zakat institutions in Muslim countries and 8% of the 50 largest Zakat Management Organizations (LAZ) in Indonesia have environmental programs as their primary portfolio. This research develops implementation models for infaq-based ecological conservation through a conceptual-analytical qualitative approach that integrates textual analysis of the Qur’an, Hadith, and fiqh with a review of secondary literature on Islamic philanthropic institutions in Indonesia from 2018 to 2025. Findings identify three applicable models: community-based (through neighborhood units RT/RW, mosques, and educational institutions), institutional (allocation of 10-15% of LAZ funds, Islamic banks, and Islamic corporations), and technology-based (digital platforms and blockchain). Implementation barriers include the awareness-practice gap (78% vs. 3.2%), long-term impact measurement, and the risk of greenwashing. This research contributes theoretically by positioning conservation within maqasid al-shariah and practically by providing an operational blueprint for zakat institutions.